2011
DOI: 10.1002/mop.26539
|View full text |Cite
|
Sign up to set email alerts
|

Application of lensed fiber collimator to miniature CWDM filter device

Abstract: are formed strongly on both side of the patch antenna, which means that this frequency depends on the three stubs and horizontal size of the patch antenna. The normalized radiation patterns of the antenna are shown in Figure 6. At 218, 338, and 400 GHz, the half-power beamwidths of the co-polarization were 144.0 , 122.4 , and 118.6 in E-plane and 88.3 , 71.3 , and 62.2 in H-plane, respectively. Cross-polarization at all frequencies is less than À10 dB. Gain is 1.61, 1.08, and 4.68 dBi and directivity is a 6.29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The work presented here deals with the possible utilization of optical lensed fiber structure for breath sensing probe. In an earlier work, we have demonstrated the lensed fiber as a tiny optical collimator [15–17] and as a CWDM device [18]. Here, an experimental study of the optical lensed fiber to work as a breath sensor is demonstrated for the first time.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The work presented here deals with the possible utilization of optical lensed fiber structure for breath sensing probe. In an earlier work, we have demonstrated the lensed fiber as a tiny optical collimator [15–17] and as a CWDM device [18]. Here, an experimental study of the optical lensed fiber to work as a breath sensor is demonstrated for the first time.…”
Section: Introductionmentioning
confidence: 91%
“…The gradient constant g is 3.8 mm −1 so the quarter‐pitch of a GIF tip is 413 μm in theorem. In terms of the best collimation and minimum divergence angle, the optimum lensed fiber was about 446 μm in our previous work [18]. The SMF with 10 μm core diameter and 125 μm cladding diameter provided by Corning was spliced to GIF.…”
Section: Operation Principle and Lensed Fiber Preparationmentioning
confidence: 99%
“…Though, gratings, tapering, and metal‐coated SPR have been used as highly sensitive RI sensing devices, the complex fabrication process increases the difficulty and the device cost for mass production. In an earlier work, we have presented a lensed fiber as a tiny optical collimator and as a CWDM device . In this article, we propose for the first time to the best of our knowledge, an RI sensor based on an optical lensed fiber.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, the authors have reported a preliminary study of helium APP's effects over the inner surface of a silica hollow optical fiber with the hole diameter of ∼100μm using a conventional set-up [15], where it was found that the liquid curvature inside HOF was changed by APP. Flexible control of the radius of curvature of the liquid core would find several applications in optical imaging and trapping [16]- [18], yet detailed investigation on this potential in liquid core fiber optics has been very limited.…”
Section: Introductionmentioning
confidence: 99%